UNDERSTANDING GURUSINA SA’O IN FLORES, NUSA TENGGARA TIMUR, INDONESIA: HEAT CONDUCTIVITY OF BUILDING ENVELOPE MATERIAL AND THERMAL COMFORT - Khotijah Lahji; Agustin Rebecca Lakawa; Bambang Susetyarto; Rita Walaretina (International Journal on Livable Space, 2018)
AbstractSa'o (traditional house) in Gurusina, Flores is a house that was designed based on the local wisdom of Ngadha tribe that is directly or indirectly constructed by considering thermal factors i.e., temperature and humidity, wind speed, and heat gain. The purpose of this paper is to examine the relationship between heat conductivity features of building envelope material towards the aspects of thermal comfort. Data gathered and analyzed through field measurements supported by structural physical figures. The research results show that first, when the study was conducted, the temperature in Gurusina exceeded the lower and upper limit of the average temperature that was considered comfort hot for Indonesians. This affects the high heat transmission through wall material so that the inside temperature is considered uncomfortable. Second, the use of half wall (exceeding 20% of the floor area) and the existence of open space around the building that has the potential to flow the wind with a speed of more than 2m/sc, can reduce the indoor heat temperature due to solar heat transmission from wall and roof materials. Key words: thermal comfort; building envelope; traditional house